West : Annual 01. - Peters, Philip; Galerie West, Den Haag (Den Haag : Galerie West, 2008)
Bad Beuys Entertainment ; Baghriche, Faycal ; Bosman, Matthijs ; Boling, John Michael ; Boudvin, Simon ; Bourgadier, Hermine ; de Bree, Harold ; Bruno, Christophe ; Chisa, Annetta Mona ; Tkacova, Lucia ; Clainchard, Matthieu ; et al.
Annnual 01 van Galerie West, Den Haag, van September 2007 - August 2008
kunstcatalogus